Diagnostic Accuracy of a Reduced Immunohistochemical Panel in Medulloblastoma Molecular Subtyping, Correlated to DNA-methylation Analysis. (April 2021) - Tauziède-Espariat, Arnault; Huybrechts, Sophie; Indersie, Emilie; Dufour, Christelle; Puget, Stéphanie; Chivet, Anaïs; Roux, Alexandre; Pagès, Mélanie; Gareton, Albane; Chrétien, Fabrice; Lechapt, Emmanuèle; Ayrault, Olivier; et al.
Abstract : Medulloblastomas (MBs) are the most frequent childhood malignant brain tumor. Four histopathologic variants and 4 genetic subgroups have been defined in the World Health Organization (WHO) 2016 Classification and constitute major risk stratification items directly affecting the patient management. Although MB subgroups have been molecularly defined, immunohistochemical surrogates are needed. The aim of our retrospective study was to evaluate the concordance between immunohistochemistry, using 4 antibodies (YAP1, GAB1, OTX2, and β-catenin), and DNA-methylation profiling in MB subgrouping. From a series of 155 MBs, the κ coefficient of concordance was almost perfect (0.90), with only 8/152 discrepant cases (no DNA-methylation analysis was available in 3 cases). Interestingly, the discrepancies mostly concerned (7/8 cases) MBs with divergent differentiations (myogenic, melanotic, and others) with all of those classified into group 3 (n=6) and group 4 (n=1) by DNA-methylation profiling. Another discrepant case concerned a WNT-activated MB (showing only 1% of immunopositive tumor cell nuclei), highlighting the difficulties of determining an appropriate β-catenin immunostaining cutoff. The high concordance of the routine immunohistochemical panel (YAP1, GAB1, OTX2, and β-catenin) and DNA-methylation profiling confirm its utility as a reliable predictive marker of molecular subtype in MBs. We analyzed the accuracy of 10 different IHC combinations for the determination of MB subtype and found that a combination of 2 antibodies (YAP1 and OTX2) allows for the successful characterization of 144 cases of 152 cases. Finally, our series extends the molecular data of the rare morphologic variant of MBs with melanotic/myogenic differentiations.